How Stella learned to talk : the groundbreaking story of the world's first talking dog - Hunger, Christina (William Morrow, an imprint of HarperCollinsPublishers, 2021)
A true story and simple guide to teaching a dog to talk from a speech-language pathologist who has taught her dog to communicate using simple paw-sized buttons associated with different words.